Dynamic capabilities of the public sector: Towards a new synthesis - Rainer Kattel (Institute for Applied Economic Research (ipea), 2022)
Covid-19 pandemic has shown how important are public sector capacities and capabilities to react to crises and re-configure existing policies and implementation practices. Prior to the pandemic, policymakers were increasingly turning their attention to challenge-driven innovation policies in order to tackle climate emergencies and other 'wicked' societal challenges. Such a 'normative turn' also assumes the existence of what can be called dynamic capabilities in the public sector. This paper offers a new synthesis of how to conceptualise dynamic capabilities in the public sector. The paper synthesises existing state capacity, public sector innovation capacity and dynamic capabilities literature. Using three brief case studies (UK's Government Digital Service, Sweden's Vinnova and the city of Barcelona), the paper discusses the origins and constitutive elements (sense-making, connecting, shaping) of dynamic capabilities. The paper also discusses how could dynamic capabilities be assessed.
Keywords: D04; H11; O38; D73; 330; dynamic capabilities; state capacity; economic development; innovation policy; entrepreneurial state